Genetic and functional characterization of loss of growth superiority of 22-ploid Morus nigra L. (2n = 22x = 308) - Raju Mondal; Vishal Kumar Jha; S. Tanya Ahmed; Prashanth Arjun Sangannavar; V. Nishitha Naik; S. Manthira Moorthy; Sunil Kumar Singh; Yogesh Mishra (Molecular Biology Reports, 2026)

Field evaluation of botanicals and organic formulations on yellow mosaic disease management and yield attributes of resistant and susceptible mungbean cultivars - Arjun Rana; Mohd Akram; Deepender Kumar; Revanasidda Aidbhavi (Crop Protection, 2026)

Robustness of the complementary frequency-shifting strategy in extended solid-state microwave reheating processes - Amit Kumar; Arjun Ghimire; Jiajia Chen (Food and Bioproducts Processing, 2026)

Surface sediment characteristics and mineralogical imprints of arid-landscape dynamics in the eastern Great Rann of Kachchh Basin, western India - Jinamoni Saikia; Niteshkumar Khonde; Kishor Katange; Arjun KV; Kamlesh Kumar (Journal of Sedimentary Environments, 2026)

Post-Harvest Deterioration in Sugarcane Juice Quality and Sucrose Under Different Harvesting Methods and Storage Duration in the Tropical Conditions - Dnyaneshwar N. Borase; Yogesh E. Thorat; Bharat M. Bhalerao; Rajeev Kumar; Rajesh U. Modi; Dinesh Singh; Arjun Singh; Santosh G. Watpade; Prashant P. Patil; Dinesh Singh (Sugar Tech, 2026)

Integrating Field Screening and Molecular Diagnostics to Assess Yellow Mosaic Disease Resistance in Selected Mungbean Varieties - Arjun Rana; Mohd. Akram; Deepender Kumar; Revanasidda Aidbhavi; Raj K. Mishra; Mukesh Srivastava; Shweta; Aditya Pratap (Current Microbiology, 2026)

Hydrogeochemical characterization and integrated groundwater quality assessment using CCME-WQI, multivariate statistics, and irrigation indices in Ambedkar Nagar Region, India - Vijayendra Pratap Dheeraj; Abhishek Kumar; Amit Kumar Rai; Avaneesh Kumar Yadav; Manvendra Singh Chauhan; Ashwani Kumar Sonkar; C. S. Singh; Arjun Prasad (Environmental Geochemistry and Health, 2026)

Revolutionizing waste management: Exploring cutting-edge innovations by CRISPR technologies in composting and vermicomposting - Niranjan Kumar Raviselvan Kavitha; Rajan Suyambu; Parthiban Pandian; Balasubramani Govindasamy; Arjun Pandian (Journal of Environmental Chemical Engineering, 2026)

Targeting NF-κB and JAK/STAT pathways in rheumatoid arthritis: emerging nanocarrier-based drug delivery approaches - G. Surendra; Jeetendra Kumar Gupta; E. Susithra; A. C. Jesudoss Prabhakaran; A. Jasmine Chandra; Vijayakumar Subash; Thukani Sathanantham Shanmugarajan; Uppuluri Varuna Naga Venkata Arjun; Konatham Teja Kumar Reddy; Ramana Hechhu (Inflammopharmacology, 2026)

Symbiont dominance and microbiome dysbiosis in wheat-aphid revealed through 16 S rRNA gene amplicon sequencing analysis - Poonam Jasrotia; Priyanka Chandra; Arjun Singh; Prem Lal Kashyap; Susheel Kumar Sharma (World Journal of Microbiology and Biotechnology, 2026)

Retraction Note: Chronic stress-mediated dysregulations in inflammatory, immune and oxidative circuitry impairs the therapeutic response of methotrexate in experimental autoimmune disease models - Rishabh Chaudhary; Mohd Akhtar Azam; Bhavana Dowand; Alpana Singh; Mujeeba Rehman; Vipul Agarwal; Anand Kumar; Arjun Singh Kaushik; Sukriti Srivastava; Siddhi Srivastava; Vikas Mishra (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A Comprehensive study on morphological, stomatal, palynological attributes and flow cytometry for differentiating anther culture derived autotetraploid from ney poovan diploid (AB) - Ramajayam Devarajan; Sanjay Chetry; Arjun Singh; Sivasankari Ragupathy; Backiyarani Suthanthiram; Mohanasundaram Arumugam; Giribabu Palaniyappan; Dinesh Kumar Agarwal; James Auxcilia; Thirugnanavel Anbazhagan; Kalpana Sathiamoorthy (Horticulture, Environment, and Biotechnology, 2026)

Characterization and Evaluation of P Solubilizing Bacteria from Forest Soils for Plant Growth Promotion - Hillol Chakdar; Pragya Saxena; M. Kumar; Arjun Singh; Samadhan Y. Bagul; Shaloo Verma; Sudipta Das; Prem Lal Kashyap; Anil Kumar Saxena (Indian Journal of Microbiology, 2026)

Emerging trends in the development of efficient CAS nucleases for meticulous gene editing in plants - Ranjit Singh Gujjar; Shehla Sherin; Sejal Batra; Arunima Mahto; Sanjay Kumar Goswami; Rajeev Kumar; Rahul Kumar Tiwari; Arjun Singh; Mala Kumari (Plant Science, 2026)

Regional distribution and seasonal histomorphology of cell types of pars distalis adenohypophysis of Gaddi goats: A comparative study between the year 2001 and the present in the context of climate change - Arjun Kumar Rao; Virender Pathak; Rajesh Rajput; Divya Gupta; Parul Shukla (Tropical Animal Health and Production, 2026)

Development of Indirect Tensile Strength (ITS) model and resilient modulus assessment considering moisture conditions on bituminous mixtures - A. Jegan Bharath Kumar; V. Sunitha; R. T. Arjun Siva Rathan; Samson Mathew (Innovative Infrastructure Solutions, 2026)

Global occurrence of particulate matter 2.5 and its toxicological effects on human health: A systematic review - Vipendra Kumar Singh; Ved Prakash; Arjun Kumar Mehara; Vikky Kumar Mahto; Anuradha Kumari; Vikas Kumar Singh; Ankit Kumar Singh (Air Quality, Atmosphere & Health, 2026)

Generation and characterization of early stage oral cancer cell line of buccal mucosa of Indian origin - Akhila George; Sudhir Nair; Kumar Prabhash; Sayujata Thakur; Poonam Gera; Arjun Singh; Pankaj Chaturvedi; Swapnil Rane; Trupti Pradhan; Subrata Sen; Madan Barkume; Dhanlaxmi Shetty; et al. (Human Cell, 2025)
Being topmost cancer in India, oral cancer management warrants discovery of novel biomarkers, treatment strategies, and targets to help with early diagnosis, treatment, and recovery. To have a continuous supply of cells, the study was aimed at generation and characterization of established cell line from buccal mucosa (BM) tumors from patients of Indian origin which can be developed as a pre-clinical tool for biomedical application. Surgically resected tumor tissue from histo-pathologically confirmed oral cancer were processed for explant culture. TBM-02 cell line was passaged and characterized for morphology and function. Further, the cell line was silenced for inflammasome pathway gene NLRP3 to evaluate its linkage with oral cancer tumorigenesis. TBM-02, successfully established from BM, was maintained up to 100 passages, exhibited epithelioid morphology, high EpCam expression and triploid ploidy with chromosomal aberrations. Novelty and human origin of TBM-02 was authenticated by Short Tandem Repeats profiling and comparison with DSMZ database. TBM-02 revealed tumorigenic potential in vitro and in vivo which was abrogated on silencing NLRP3. Increased expression of NLRP3, hallmark of chronic inflammation in TBM-02, was validated at protein and gene level and in xenograft. TBM-02 demonstrated migratory potential and was found to be a sensitive tool to study drug response. RNA sequencing demonstrated upregulation of oral cancer-associated genes and pathways. Thus, in current study, we have reported development of novel cell line from early-stage buccal mucosa cancer patient which has a strong potential to be developed and to be used as pre-clinical model for improving oral cancer management and therapeutics. Graphical Abstract

Invigorating Soil-Plant Productivity to Improve Fruit Quality in Cherry Tomato Through Multi-Modal Application of Cyanobacteria - Deepti Varsha; Akanksha Bhardwaj; Radha Prasanna; Awani Kumar Singh; Shalini Gaur Rudra; Sangeeta Paul; Ravi Mourthy Nivedha; Aditi Arjun Tayade; Yashbir Singh Shivay (Journal of Soil Science and Plant Nutrition, 2025)

Evaluation of lymphoid defects in specific inborn errors of immunity using a single-tube multicolor flow cytometry assay - Reja Tanveer; Sanchi Chawla; Saniya Sharma; Ankur Jindal; Manpreet Dhaliwal; Gurjit Kaur; Pallavi L. Nadig; Kanika Arora; Taru Goyal; Arjun Ram; Satish Sharma; Pandiarajan Vignesh; et al. (Immunogenetics, 2025)

A convolutional neural network-based segmentation approach for oil spill detection in satellite imagery with explainable AI - Arjun Kumar Bose Arnob; M. F. Mridha; Meshal Alfarhood; Dunren Che; Mejdl Safran (Earth Science Informatics, 2025)

Exploring the effectiveness of bio-formulations from various cattle breeds on pea growth and yield - Arjun Singh; Rameshwar Kumar; Shorya Kapoor; M. S. Bhadwal; A. P. Singh (Organic Agriculture, 2025)

Design and Validation of a Low-Cost, Portable Arduino-Based Platform for Assessing Physicochemical Drinking Water Quality Across Urban and Peri-urban Areas of Delhi and Surrounding Regions - Arjun Singh; Rahul Arya; Nikki Choudhary; Navraj Poudel; Poonam Arora; K. K. Maurya; T. K. Mandal; S. K. Sharma; Prashant Kumar; Saurabh Pathak; R. P. Pant (Water Conservation Science and Engineering, 2025)

Alkaloids as neuroprotectors: targeting signaling pathways in neurodegenerative diseases - Biswajit Kumar Utpal; Md Al Amin; Mehrukh Zehravi; Sherouk Hussein Sweilam; Uppuluri Varuna Naga Venkata Arjun; Y. Bala Madhuri; Jeetendra Kumar Gupta; Lavanya Yaidikar; Tanuja Tummala; R. Suseela; Akiladevi Durairaj; Konatham Teja Kumar Reddy; et al. (Molecular and Cellular Biochemistry, 2025)

Seismic hazard mapping of Arunachal Pradesh: Integrating updated data and logic tree methodology - Aman Kumar; Satyaprakash Mishra; Arjun Sil (Journal of Earth System Science, 2025)

Host delivered RNA interference in apple cv. Red Chief for mediating resistance against Diplocarpon coronariae - Abhishek Kumar; Neha Kumari; Arjun Chauhan; Manju Modgil (Journal of Plant Pathology, 2025)

Therapeutic potential of flavonoids in neuroprotection: brain and spinal cord injury focus - Md. Faysal; Md Al Amin; Mehrukh Zehravi; Sherouk Hussein Sweilam; Uppuluri Varuna Naga Venkata Arjun; Jeetendra Kumar Gupta; Thukani Sathanantham Shanmugarajan; Sarandeep Shanmugam Prakash; Girija Dayalan; Saravanakumar Kasimedu; Y Bala Madhuri; Konatham Teja Kumar Reddy; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Exploring natural products as apoptosis modulators in cancers: insights into natural product-based therapeutic strategies - Biswajit Kumar Utpal; Hasna Bouenni; Mehrukh Zehravi; Sherouk Hussein Sweilam; Mohammad Rakib Mortuza; Uppuluri Varuna Naga Venkata Arjun; Thukani Sathanantham Shanmugarajan; Ponnammal Ganesan Mahesh; Pathakota Roja; Ravi Kalyan Dodda; E. Thilagam; Mohammed Saeed Almahjari; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Physiochemical insights into substrate-diatom adhesion: Influence of surface properties on biofilm dynamics and productivity - Manikandan Sivakumar; Inbakandan Dhinakarasamy; Clarita Clements; Naren Kumar Thirumurugan; Subham Chakraborty; Anu Chandrasekar; Jeevitha Vinayagam; Kumar Chandrasekaran; Thirugnanasambandam Rajendran; S.A.S. Suriyaraj; K.R. Arjun Aditiya (Algal Research, 2025)

RETRACTED ARTICLE: Chronic stress-mediated dysregulations in inflammatory, immune and oxidative circuitry impairs the therapeutic response of methotrexate in experimental autoimmune disease models - Rishabh Chaudhary; Mohd Akhtar Azam; Bhavana Dowand; Alpana Singh; Mujeeba Rehman; Vipul Agarwal; Anand Kumar; Arjun Singh Kaushik; Sukriti Srivastava; Siddhi Srivastava; Vikas Mishra (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Molecular Mechanistic of Zn-Solubilizing Bacteria for Agronomic Eminence: Recent Updates and Futuristic Development - Nitu Rani; Arjun Chauhan; Sukhminderjit Kaur; Manoj Kumar Solanki; Manikant Tripathi; Devendra Jain; Shraddha Singh; Sudhir K. Upadhyay; Gurparteek Kaur (Journal of Plant Growth Regulation, 2025)

Pre- and post-anthesis dry matter and nutrient accumulation, partitioning, remobilization and crop productivity of maize under the long-term integrated crop management practices - Anamika Barman; Vijay Pooniya; R.R. Zhiipao; Niraj Biswakarma; Dinesh Kumar; Kajal Das; Y.S. Shivay; S.S. Rathore; Nilutpal Saikia; Santanu Kundu; Arjun Singh; M.C. Meena; et al. (European Journal of Agronomy, 2025)

The dynamic crosslinking between gut microbiota and inflammation during aging: reviewing the nutritional and hormetic approaches against dysbiosis and inflammaging - Sakshi Chaudhary; Pardeep Kaur; Thokchom Arjun Singh; Kaniz Shahar Bano; Ashish Vyas; Alok Kumar Mishra; Prabhakar Singh; Mohammad Murtaza Mehdi (Biogerontology, 2025)

Unravelling the proteome of Saccharum officinarum cv. BO91 for novel defense-related proteins during C. falcatum infection - Ranjit Singh Gujjar; Deeksha Joshi; Sanjay Kumar Goswami; Rajeev Kumar; Arjun Singh; Atul Kumar Upadhyay (Acta Physiologiae Plantarum, 2025)

Effects of geographical variation on the phytochemicals gallic acid, corilagin, and ellagic acid, as well as medicinal properties of Emblica officinalis Gaertn (Fruit) - Yashika Gandhi; Sujeet K. Mishra; Vijay Kumar; Hemant Rawat; Ravi Kumar; Ravindra Singh; Arjun Singh; Ch Venkata Narasimhaji; Narayanam Srikanth; Rabinarayan Acharya (Food and Humanity, 2024)

Harnessing the power of clustered regularly interspaced short palindromic repeats (CRISPR) based microfluidics for next-generation molecular diagnostics - Rasanpreet Kaur; Saurabh Gupta; Arjun Chauhan; Vidhi Mishra; Manish Kumar Sharma; Jitendra Singh (Molecular Biology Reports, 2024)

Correction: Factors influencing the distribution of the endangered hispid hare in Bardia National Park, Nepal - Arjun Thapa; Rabin Bahadur K. C.; Rajan Prasad Paudel; Rabin Kadariya; Rima G. C.; Ranjita Khadka; Laxmi Raj Joshi; Shyam Kumar Shah; Sagar Dahal (Mammalian Biology, 2024)

Factors influencing the distribution of the endangered hispid hare in Bardia National Park, Nepal - Arjun Thapa; Rabin Bahadur K. C.; Rajan Prasad Paudel; Rabin Kadariya; Rima G. C.; Ranjita Khadka; Laxmi Raj Joshi; Shyam Kumar Shah; Sagar Dahal (Mammalian Biology, 2024)

Standardization of Organically Chickpea Cultivation in Red and Lateritic Soils Through Sole and Combined Uses of Bulky Organic Manures - Saikat Biswas; Rupa Das; Ashok Thakur; Anup Mahto; Arjun Kumar Mahto (Journal of Soil Science and Plant Nutrition, 2024)

A New Multiplex PCR Assay Reveals the Occurrence of E. bangladeshi alongside E. histolytica and E. moshkovskii in Eastern India - Sanjib Kumar Sardar; Sweety Mal; Ajanta Ghosal; Tapas Haldar; Akash Prasad; Chayanika Roy; Arjun Ghosh; Yumiko Saito-Nakano; Seiki Kobayashi; Shanta Dutta; Tomoysohi Nozaki; Sandipan Ganguly (Acta Parasitologica, 2024)

Study of Luminescence Phenomena of Tb (III) Containing Fluroquinoline for Application in Optoelectronic Devices - Poonam Kumari; Vaishnavi Lather; Arjun Malik; Pratibha Ahlawat; Rajesh Kumar (Journal of Fluorescence, 2024)

Evaporative cooling and sensible heat recovery enable practical waste-heat driven water purification - Ankush Kumar Jaiswal; Rishabh Srivastava; Arjun Jayakumar; Aqbal Ahmad; Gayathri Naidu; Jaichander Swaminathan (Desalination, 2024)

Alkaloid-based modulators of the PI3K/Akt/mTOR pathway for cancer therapy: Understandings from pharmacological point of view - Fatima Zohra Mokhfi; Md Al Amin; Mehrukh Zehravi; Sherouk Hussein Sweilam; Uppuluri Varuna Naga Venkata Arjun; Jeetendra Kumar Gupta; Bhaskar Vallamkonda; Anitha Balakrishnan; Manjula Challa; Jyoti Singh; P. Dharani Prasad; Syed Salman Ali; et al. (Chemico-Biological Interactions, 2024)

Optimising miniaturised hydrocyclones for enhanced separation of microplastics - Te Bu; Diego Mesa; Arjun Kumar Pukkella; Pablo R. Brito-Parada (Chemical Engineering Journal, 2024)

Colletotrichum falcatum infection influences the abundance of sucrose transporters and disease resistant proteins in sugarcane stalk - Ranjit Singh Gujjar; Rajeev Kumar; Sanjay Kumar Goswami; Arjun Singh; Ananya Baidya (Journal of Plant Biochemistry and Biotechnology, 2024)

Clinical and Genomic Perspective of SARS CoV-2 Infection in Liver Disease Patients: A Single-Centre Retrospective Study - Reshu Agarwal; Arjun Bhugra; Pramod Gautam; Varun Suroliya; Ruchita Chhabra; Amit Pandey; Prince Garg; Pooja Rao; Rosmy Babu; Guresh Kumar; Chhagan Bihari; Debajyoti Bhattacharyya; et al. (Current Microbiology, 2024)

Sub-surface drip-fertigation and legume residue improved maize yield and nitrogen use - Arjun Singh; Anchal Dass; Susama Sudhishri; V. K. Singh; Kapila Shekhawat; M. C. Meena; R. N. Sahoo; Soora Naresh Kumar; P. K. Upadhyay; Shiva Dhar; Kadagonda Nithinkumar (Nutrient Cycling in Agroecosystems, 2024)

Appraisal on suitable landfill site selection for municipal solid waste disposal using GIS and MIF methods - Nitin Liladhar Rane; Suraj Kumar Mallick; Arjun Saha; Chaitanya Baliram Pande; Jayesh Rane; Ranjan Roy; Fahad Alshehri; Neyara Radwan (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Correction to: Comprehensive Profiling of Secreted Factors in the Cerebrospinal Fluid of Moyamoya Disease Patients - Kumar Abhinav; Alex G. Lee; Arjun V. Pendharkar; Mark Bigder; Anthony Bet; Yael Rosenberg-Hasson; Michelle Y. Cheng; Gary K. Steinberg (Translational Stroke Research, 2024)

Comprehensive Profiling of Secreted Factors in the Cerebrospinal Fluid of Moyamoya Disease Patients - Kumar Abhinav; Alex G. Lee; Arjun V. Pendharkar; Mark Bigder; Anthony Bet; Yael Rosenberg-Hasson; Michelle Y. Cheng; Gary K. Steinberg (Translational Stroke Research, 2024)
Moyamoya disease (MMD) is characterized by progressive occlusion of the intracranial internal carotid arteries, leading to ischemic and hemorrhagic events. Significant clinical differences exist between ischemic and hemorrhagic MMD. To understand the molecular profiles in the cerebrospinal fluid (CSF) of MMD patients, we investigated 62 secreted factors in both MMD subtypes (ischemic and hemorrhagic) and examined their relationship with preoperative perfusion status, the extent of postoperative angiographic revascularization, and functional outcomes. Intraoperative CSF was collected from 32 control and 71 MMD patients (37 ischemic and 34 hemorrhagic). Multiplex Luminex assay analysis showed that 41 molecules were significantly elevated in both MMD subtypes when compared to controls, including platelet-derived growth factor-BB (PDGF-BB), plasminogen activator inhibitor 1 (PAI-1), and intercellular adhesion molecule 1 (ICAM1) ( p < 0.001). Many of these secreted proteins have not been previously reported in MMD, including interleukins (IL-2, IL-4, IL-5, IL-7, IL-8, IL-9, IL-17, IL-18, IL-22, and IL-23) and C-X-C motif chemokines (CXCL1 and CXCL9). Pathway analysis indicated that both MMD subtypes exhibited similar cellular/molecular functions and pathways, including cellular activation, migration, and inflammatory response. While neuroinflammation and dendritic cell pathways were activated in MMD patients, lipid signaling pathways involving nuclear receptors, peroxisome proliferator-activated receptor (PPAR), and liver X receptors (LXR)/retinoid X receptors (RXR) signaling were inhibited. IL-13 and IL-2 were negatively correlated with preoperative cerebral perfusion status, while 7 factors were positively correlated with the extent of postoperative revascularization. These elevated cytokines, chemokines, and growth factors in CSF may contribute to the pathogenesis of MMD and represent potential future therapeutic targets.

Dynamicity and extractability of hydro-alcoholic solvents for Tinospora cordifolia stem: an investigation for target-oriented traditional drug discovery based on biologically active phytocompounds - Kalyan Hazra; Deepak Kumar; Sudipto Debnath; Susmita Mondal; Manoj Batule; Sreya Dutta; Arjun Singh; Ravindra Singh; Anupam Kumar Mangal (Vegetos, 2024)

Exploring the asymmetric effect of fiscal policy instruments in encountering environmental degradation: proposing an SDG framework for India - Arjun; Bibhuti Ranjan Mishra; Aviral Kumar Tiwari (Environmental Science and Pollution Research, 2024)

Association of lightning with LCL, EL, humidity at 850 mb and at 200 mb during various CAPE, over northern India - Deen Mani Lal; Nandivada Umakanth; Manoj Arjun Domkawale; Venkatachalam Gopalakrishnan; Manoj Kumar Srivastava; Sunil Dnyandeo Pawar (Science of The Total Environment, 2024)

The impact of radio-chemotherapy on tumour cells interaction with optimal control and sensitivity analysis - Arjun Kumar; Uma S. Dubey; Balram Dubey (Mathematical Biosciences, 2024)

Insights into Cow Dung-Based Bioformulations for Sustainable Plant Health and Disease Management in Organic and Natural Farming System: a Review - Shweta Sagar; Arjun Singh; Jyoti Bala; Rakesh Chauhan; Rameshwar Kumar; Ravi Kant Bhatia; Abhishek Walia (Journal of Soil Science and Plant Nutrition, 2024)

Late Quaternary deformation, strain partitioning, and fold-thrust belt widening in the Eastern Himalayan Syntaxis, India - Ishwar Singh; R. Jayangondaperumal; Arjun Pandey; Rao Singh Priyanka; Rajeeb Lochan Mishra; P. Morthekai; Shraddha Jagtap; Pradeep Srivastava; Pankaj Kumar; Sundeep Chopra (Tectonophysics, 2024)

Harnessing Rhizospheric Microbes for Eco-friendly and Sustainable Crop Production in Saline Environments - Sanjay K. Goswami; Abhijeet S. Kashyap; Rajeev Kumar; Ranjit Singh Gujjar; Arjun Singh; Nazia Manzar (Current Microbiology, 2024)

Epigenetic regulation during meiosis and crossover - K. V. S. K. Arjun Chowdary; Ramswaroop Saini; Amit Kumar Singh (Physiology and Molecular Biology of Plants, 2023)

Susceptibility of different Basmati rice varieties to bakanae disease and it’s integrated management in rice cultivar Pusa Basmati 1121 - Ravindra Kumar; Anuja Gupta; Rajesh Kumar Meena; Bishnu Maya Bashyal; Kumkum Verma; Arjun Singh (Indian Phytopathology, 2023)

Understanding the physical state and tectonics of Eastern Himalaya using coda wave attenuation - Rohtash Kumar; Amritansh Rai; Raghav Singh; S C Gupta; Arjun Kumar; S P Singh; Prashant Kumar Singh; S P Maurya; Vinay Kumar; G P Singh (Journal of Earth System Science, 2023)

A comprehensive review and recent advances in dry mineral classification - Arjun Kumar Pukkella; Jan J. Cilliers; Kathryn Hadler (Minerals Engineering, 2023)

Internal feed preheating necessary for energy-efficient modular multi-effect membrane distillation - Rishabh Srivastava; Ankush Kumar Jaiswal; Arjun Jayakumar; Jaichander Swaminathan (Desalination, 2023)

Aging, oxidative stress and degenerative diseases: mechanisms, complications and emerging therapeutic strategies - Mani Raj Chaudhary; Sakshi Chaudhary; Yogita Sharma; Thokchom Arjun Singh; Alok Kumar Mishra; Shweta Sharma; Mohammad Murtaza Mehdi (Biogerontology, 2023)

Emblica officinalis: A promising herb confining versatile applications - Yashika Gandhi; Jyotika Grewal; Vipin Jain; Hemant Rawat; Sujeet K. Mishra; Vijay Kumar; Ravi Kumar; Santosh Kumar Shakya; Preeti Sharma; Daljeet Singh Dhanjal; Shyam Baboo Prasad; Vaibhav Charde; et al. (South African Journal of Botany, 2023)

Sugarcane Stalk Traits for High Throughput Phenotyping in Restricted Irrigation Regimes - Vasantha Srinivasavedantham; Arun Kumar Raja; Krishnapriya Vengavasi; Arjun Shaligram Tayade; Anusha Shareef; Hemaprabha Govindakurup (Sugar Tech, 2023)

Exploring the asymmetric effect of fiscal decentralization on economic growth and environmental quality: evidence from India - Bibhuti Ranjan Mishra; Arjun; Aviral Kumar Tiwari (Environmental Science and Pollution Research, 2023)

Thermodynamic characteristics of marine atmospheric boundary layer across frontal regions of the Indian Ocean Sector of the Southern Ocean based on three field campaigns - Shaikh Neha Salim; Arjun Adhikari; Harilal B. Menon; N.V.P. Kiran Kumar; Rajeev Kunjukrishnapillai (Atmospheric Research, 2023)

Energy-Carbon Footprint, Productivity and Profitability of Barley Cultivars under Contrasting Tillage-Residue Managements in Semi-Arid Plains of North-West India - Malu Ram Yadav; Sudesh Kumar; Biswaranjan Behera; Ved Prakash Yadav; Ajit Singh Khrub; Lala Ram Yadav; Kailash Chandra Gupta; Om Prakash Meena; Arjun Singh Baloda; Md Basit Raza; Rabindra Kumar Panda; Milan Kumar Lal (Journal of Soil Science and Plant Nutrition, 2023)

Tropical cyclone risk assessment of Port Blair, Andaman Islands, India by using numerical modelling and geospatial techniques - Hamid Varikkodan; S Balaji; S Arjun; Kajal Kumar Mandal (Journal of Earth System Science, 2023)

Aerosol-boundary layer dynamics and its effect on aerosol radiative forcing and atmospheric heating rate in the Indian Ocean sector of Southern Ocean - S. Neha Salim; Arjun Adhikari; Atiba A. Shaikh; Harilal B. Menon; N.V.P. Kiran Kumar; K. Rajeev (Science of The Total Environment, 2023)

Photoperiodic Induction and Synchronization of Flowering in Sugarcane Hybrids for Breeding Programs - Krishnapriya Vengavasi; Vasantha Srinivasavedantham; Arun Kumar Raja; Arjun Shaligram Tayade; Bakshi Ram (Sugar Tech, 2023)

Climate change and more disturbed land-use types will further the invasion of a non-native annual grass, Ventenata dubia - Arjun Adhikari; Jane Mangold; Kumar P. Mainali; Lisa J. Rew (Biological Invasions, 2023)
Identification of suitable habitat for invasive weeds and their projected infestation extent across different land use cover types under a changing climate is crucial for the broad management goals of prevention, detection, and rapid response. In this study, we adopted an ensemble approach of species distribution models to project potential habitat of the invasive annual grass, Ventenata dubia , within the Gallatin County and along its road corridors, in Montana, USA, under current and future climates. The model prediction of V. dubia habitat was excellent with an AUC value of > 0.90. The climate predictors with most influence on V . dubia occurrence were precipitation, potential evapo-transpiration, relative humidity, vapor pressure deficit, and solar radiation for growing season months. Under current climate, the model projected 243 and 1,371 km 2 coverage of V. dubia along road corridors and the entire County, respectively. The projected coverage of V. dubia was greatest for road corridors (239% under RCP4.5 and 302% under RCP8.5) compared to that of Gallatin County (127% under RCP4.5 and 241% under RCP8.5). Among the land use cover types, the model projected greatest expansion of V. dubia across agriculture land with 425% and 484%, and grasslands with 278% and 442% under RCP4.5 and RCP8.5 respectively. Our modelling approach suggests that the changing climate will facilitate spread and establishment of non-native species in disturbed habitats. We conclude that V. dubia with a short history of invasion is expanding at an alarming rate and requires greater investment in detection and monitoring to prevent further expansion.

Bacterial chitinases: genetics, engineering and applications - Murugan Kumar; Hillol Chakdar; Kuppusamy Pandiyan; Shobit Thapa; Mohammad Shahid; Arjun Singh; Alok Kumar Srivastava; Anil Kumar Saxena (World Journal of Microbiology and Biotechnology, 2022)

Moment tensor solutions of some regional events using 3-component single station waveform data - Rohtash Kumar; Arjun Kumar; S C Gupta; S P Singh; Rajeev Saran Ahluwalia; Raghav Singh (Journal of Earth System Science, 2022)

Prediction of focal image for solar parabolic dish concentrator with square facets—an analytical model - Arjun Singh Kopalakrishnaswami; Reyhaneh Loni; Gholamhassan Najafi; Sendhil Kumar Natarajan (Environmental Science and Pollution Research, 2022)

Productivity and Nutrient Dynamic of Legume in a Maize-legume Cropping System are Influenced by Biomulches Under No-tillage System - Joy Kumar Dey; Binoy Kumar Saren; Ashim Debnath; Bharat Arjun Gudade; Satyapriya Singh; Amit Kumar; Jnana Bharati Palai; Ahmed Gaber; Akbar Hossain (International Journal of Plant Production, 2022)

Historical overview of power generation in solar parabolic dish collector system - Susant Kumar Sahu; Arjun Singh Kopalakrishnaswami; Sendhil Kumar Natarajan (Environmental Science and Pollution Research, 2022)

Cytotoxic effect of plant extract-based nanoparticles on cancerous cells: a review - Jyotika Grewal; Vijay Kumar; Hemant Rawat; Yashika Gandhi; Ravindra Singh; Arjun Singh; Gajji Babu; Narayanam Srikanth; Sujeet K. Mishra (Environmental Chemistry Letters, 2022)

TOXGB: Teamwork Optimization Based XGBoost model for early identification of post-traumatic stress disorder - Sonam Gupta; Lipika Goel; Arjun Singh; Abhay Kumar Agarwal; Raushan Kumar Singh (Cognitive Neurodynamics, 2022)

In silico, in vitro screening of antioxidant and anticancer potentials of bioactive secondary metabolites from an endophytic fungus (Curvularia sp.) from Phyllanthus niruri L - Arjun Kumar Kalimuthu; Pavadai Parasuraman; Pandian Sivakumar; Sankaranarayanan Murugesan; Sankarganesh Arunachalam; Sureshbabu Ram Kumar Pandian; Vigneshwaran Ravishankar; Damodar Nayak Ammunje; Muthukumar Sampath; Theivendran Panneerselvam; Selvaraj Kunjiappan (Environmental Science and Pollution Research, 2022)

Potential Health Risks Associated with the Heavy Metal Content in Commonly Consumed Food from Prakasam District of Andhra Pradesh, India - Arjun L. Khandare; Vakdevi Validandi; Ravi Prakash Jamalpur; Srinivas Dheeravath; Srinivasu Kurella; Anitha Chauhan; Naveen kumar Boiroju; Longvah Thingnganing (Biological Trace Element Research, 2022)

Horticultural crops tackling stresses: genetic and epigenetic alterations - Samriti Sharma; Arjun Chauhan; Raj Kumar; Sneha Dobhal; Rajinder Kaur; Krishan Kumar; Kamlesh Verma (Genetic Resources and Crop Evolution, 2022)

Comparative study of modified conical cavity receiver with other receivers for solar paraboloidal dish collector system - Arjun Singh Kopalakrishnaswami; Sendhil Kumar Natarajan (Environmental Science and Pollution Research, 2022)

ESOPA: a GUI-based MATLAB platform for estimation of earthquake spectral source parameters, inelastic attenuation, high-frequency decay kappa, and fmax-model - Rohtash Kumar; Raghav Singh; Subhash Chander Gupta; Amritansh Rai; Prashant Singh; Aquib Ali; Arjun Kumar; Satya Prakash Maurya (Arabian Journal of Geosciences, 2021)

Arsenic-induced uterine apoptotic damage is protected by ethyl acetate fraction of Camellia sinensis (green tea) via Bcl-2-BAX through NF-κB regulations in Wistar rats - Arindam Dey; Hasina Perveen; Arjun L Khandare; Amrita Banerjee; Smarajit Maiti; Suryashis Jana; Asit Kumar Chakraborty; Sandip Chattopadhyay (Environmental Science and Pollution Research, 2021)

Groundwater vulnerability assessment using water quality index (WQI) under geographic information system (GIS) framework in parts of Uttar Pradesh, India - Abhishek Kumar Chaurasia; H. K. Pandey; S. K. Tiwari; Prashant Pandey; Arjun Ram (Sustainable Water Resources Management, 2021)

Enhancement in Plant Growth and Zinc Biofortification of Chickpea (Cicer arietinum L.) by Bacillus altitudinis - Prity Kushwaha; Ruchi Srivastava; Kuppusamy Pandiyan; Arjun Singh; Hillol Chakdar; Prem Lal Kashyap; Ajay Kumar Bhardwaj; Kumar Murugan; Nanjappan Karthikeyan; Samadhan Yuvraj Bagul; Alok Kumar Srivastava; Anil Kumar Saxena (Journal of Soil Science and Plant Nutrition, 2021)

Correction to: Future distribution of invasive weed species across the major road network in the state of Montana, USA - Arjun Adhikari; Lisa J. Rew; Kumar P. Mainali; Subodh Adhikari; Bruce D. Maxwell (Regional Environmental Change, 2020)

A rapid and sensitive method to detect SARS-CoV-2 virus using targeted-mass spectrometry - Praveen Singh; Rahul Chakraborty; Robin Marwal; V. S. Radhakrishan; Akash Kumar Bhaskar; Himanshu Vashisht; Mahesh S. Dhar; Shalini Pradhan; Gyan Ranjan; Mohamed Imran; Anurag Raj; Uma Sharma; et al. (Journal of Proteins and Proteomics, 2020)

Future distribution of invasive weed species across the major road network in the state of Montana, USA - Arjun Adhikari; Lisa J. Rew; Kumar P. Mainali; Subodh Adhikari; Bruce D. Maxwell (Regional Environmental Change, 2020)
Invasive plant species are a significant global problem, with the potential to alter structure and function of ecosystems and cause economic damage to managed landscapes. An effective course of action to reduce the spread of invasive plant species is to identify potential habitat incorporating changing climate scenarios. In this study, we used a suite of species distribution models (SDMs) to project habitat suitability of the eleven most abundant invasive weed species across road networks of Montana, USA, under current (2005) conditions and future (2040) projected climates. We found high agreement between different model predictions for most species. Among the environmental predictors, February minimum temperature, monthly precipitation, solar radiation, and December vapor pressure deficit accounted for the most variation in projecting habitat suitability for most of the invasive weed species. The model projected that habitat suitability along roadsides would expand for seven species ranging from + 5 to + 647% and decline for four species ranging from − 11 to − 88% under high representative concentration pathway (RCP 8.5) greenhouse gas (GHG) trajectory. When compared with current distribution, the ensemble model projected the highest expansion habitat suitability with six-fold increase for St. John’s Wort ( Hypericum perforatum ), whereas habitat suitability of leafy spurge ( Euphorbia esula ) was reduced by − 88%. Our study highlights the roadside areas that are currently most invaded by our eleven target species across 55 counties of Montana, and how this will change with climate. We conclude that the projected range shift of invasive weeds challenges the status quo, and requires greater investment in detection and monitoring to prevent expansion. Though our study focuses across road networks of a specific region, we expect our approach will be globally applicable as the predictions reflect fundamental ecological processes.

Molecular detection and in silico characterization of cold shock protein coding gene (cspA) from cold adaptive Pseudomonas koreensis - Srikant Awasthi; Anjney Sharma; Pragya Saxena; Jagriti Yadav; K. Pandiyan; M. Kumar; Arjun Singh; Hillol Chakdar; Arpan Bhowmik; Prem L. Kashyap; Alok K. Srivastava; Anil K. Saxena (Journal of Plant Biochemistry and Biotechnology, 2019)

Efficient methanol-degrading aerobic bacteria isolated from a wetland ecosystem - Kavitha Thulasi; Arjun Jayakumar; Aneesh Balakrishna Pillai; Vinod Kumar Gopalakrishnapillai Sankaramangalam; Harikrishnan Kumarapillai (Archives of Microbiology, 2018)

Characterization of a novel asparaginase from soil metagenomic libraries generated from forest soil - Jaya Kumar Arjun; Balakrishna Pillai Aneesh; Thulasi Kavitha; Kumarapillai Harikrishnan (Biotechnology Letters, 2018)

Source Parameters and High Frequency Characteristics of Local Events (0.5 ≤ M L ≤ 2.9) Around Bilaspur Region of the Himachal Himalaya - Vandana; Ashwani Kumar; S. C. Gupta; O. P. Mishra; Arjun Kumar; Sandeep (Pure and Applied Geophysics, 2017)

Evaluating the effects of ground motion parameters on response spectra in Uttarakhand Himalayas, India - Himanshu Mittal; Yih-Min Wu; Ashok Kumar; Arjun Kumar; Babita Sharma (Arabian Journal of Geosciences, 2016)

Dynamics of a low‐density tiger population in Southeast Asia in the context of improved law enforcement - Somphot Duangchantrasiri; Mayuree Umponjan; Saksit Simcharoen; Anak Pattanavibool; Soontorn Chaiwattana; Sompoch Maneerat; N. Samba Kumar; Devcharan Jathanna; Arjun Srivathsa; K. Ullas Karanth (Conservation Biology, 2016)
Recovering small populations of threatened species is an important global conservation strategy. Monitoring the anticipated recovery, however, often relies on uncertain abundance indices rather than on rigorous demographic estimates. To counter the severe threat from poaching of wild tigers ( Panthera tigris ), the Government of Thailand established an intensive patrolling system in 2005 to protect and recover its largest source population in Huai Kha Khaeng Wildlife Sanctuary. Concurrently, we assessed the dynamics of this tiger population over the next 8 years with rigorous photographic capture‐recapture methods. From 2006 to 2012, we sampled across 624–1026 km 2 with 137–200 camera traps. Cameras deployed for 21,359 trap days yielded photographic records of 90 distinct individuals. We used closed model Bayesian spatial capture‐recapture methods to estimate tiger abundances annually. Abundance estimates were integrated with likelihood‐based open model analyses to estimate rates of annual and overall rates of survival, recruitment, and changes in abundance. Estimates of demographic parameters fluctuated widely: annual density ranged from 1.25 to 2.01 tigers/100 km 2 , abundance from 35 to 58 tigers, survival from 79.6% to 95.5%, and annual recruitment from 0 to 25 tigers. The number of distinct individuals photographed demonstrates the value of photographic capture–recapture methods for assessments of population dynamics in rare and elusive species that are identifiable from natural markings. Possibly because of poaching pressure, overall tiger densities at Huai Kha Khaeng were 82–90% lower than in ecologically comparable sites in India. However, intensified patrolling after 2006 appeared to reduce poaching and was correlated with marginal improvement in tiger survival and recruitment. Our results suggest that population recovery of low‐density tiger populations may be slower than anticipated by current global strategies aimed at doubling the number of wild tigers in a decade.

Source study of M w 5.4 April 4, 2011 India–Nepal border earthquake and scenario events in the Kumaon–Garhwal Region - Himanshu Mittal; Ashok Kumar; Yih-Min Wu; Kamal; Arjun Kumar (Arabian Journal of Geosciences, 2016)

Effect of azimuthal coverage of an earthquake on moment tensor solutions estimated by waveform inversion - Rohtash Kumar; Subhash Chander Gupta; Arjun Kumar (Arabian Journal of Geosciences, 2015)

Identifying species, sex and individual tigers and leopards in the Malenad-Mysore Tiger Landscape, Western Ghats, India - Samrat Mondol; N. Samba Kumar; Arjun Gopalaswamy; Kartik Sunagar; K. Ullas Karanth; Uma Ramakrishnan (Conservation Genetics Resources, 2015)

Analysis of ground motion in Delhi from earthquakes recorded by strong motion network - Himanshu Mittal; Ashok Kumar; Arjun Kumar; Rohtash Kumar (Arabian Journal of Geosciences, 2015)

Determination and identification of focal mechanism solutions for Himalayan earthquakes from waveform inversion employing ISOLA software - Rohtash Kumar; S. C. Gupta; Arjun Kumar (Natural Hazards, 2015)

Pyrene Degradation by Biosurfactant Producing Bacterium Stenotrophomonas maltophilia - Arjun Singh; Kaushelendera Kumar; Alok Kumar Pandey; Anamika Sharma; Shashi Bala Singh; Kanika Kumar; Anju Arora; Lata Nain (Agricultural Research, 2015)

Source parameters and f max in lower Siang region of Arunachal lesser Himalaya - Rohtash Kumar; S. C. Gupta; Arjun Kumar; Himanshu Mittal (Arabian Journal of Geosciences, 2015)

Estimation of source parameters of local earthquakes in the environs of Koldam site - Vinod Paidi; Ashwani Kumar; S. C. Gupta; Arjun Kumar (Arabian Journal of Geosciences, 2015)

Seismicity and source parameters of local earthquakes in Bilaspur region of Himachal Lesser Himalaya - Ashwani Kumar; Arjun Kumar; S. C. Gupta; A. K. Jindal; Vandana Ghangas (Arabian Journal of Geosciences, 2014)

Correlation of human S100A12 (EN-RAGE) and high-sensitivity C-reactive protein as gingival crevicular fluid and serum markers of inflammation in chronic periodontitis and type 2 diabetes - A. R. Pradeep; Santosh S. Martande; Sonender Pal Singh; Deepak Kumar Suke; Arjun P. Raju; Savitha B. Naik (Inflammation Research, 2014)

Identification and Characterization of a FYVE Domain from the Early Diverging Eukaryote Giardia lamblia - Abhishek Sinha; Sananda Mandal; Sumana Banerjee; Arjun Ghosh; Sandipan Ganguly; Alok Kumar Sil; Srimonti Sarkar (Current Microbiology, 2011)

Cerebro-spinal and renal ochronosis: A rare case report - Sunil Kumar Nanda; D. R. Suresh; A. Vamseedhar; K. Pratibha; B. Arjun (Indian Journal of Clinical Biochemistry, 2010)

Bayesian inference in camera trapping studies for a class of spatial capture–recapture models - J. Andrew Royle; K. Ullas Karanth; Arjun M. Gopalaswamy; N. Samba Kumar (Ecology, 2009)
We develop a class of models for inference about abundance or density using spatial capture–recapture data from studies based on camera trapping and related methods. The model is a hierarchical model composed of two components: a point process model describing the distribution of individuals in space (or their home range centers) and a model describing the observation of individuals in traps. We suppose that trap‐ and individual‐specific capture probabilities are a function of distance between individual home range centers and trap locations. We show that the models can be regarded as generalized linear mixed models, where the individual home range centers are random effects. We adopt a Bayesian framework for inference under these models using a formulation based on data augmentation. We apply the models to camera trapping data on tigers from the Nagarahole Reserve, India, collected over 48 nights in 2006. For this study, 120 camera locations were used, but cameras were only operational at 30 locations during any given sample occasion. Movement of traps is common in many camera‐trapping studies and represents an important feature of the observation model that we address explicitly in our application.

Thermal Injury Prediction During Cryoplasty Through In Vitro Characterization of Smooth Muscle Cell Biophysics and Viability - Saravana Kumar Balasubramanian; Ramji T. Venkatasubramanian; Arjun Menon; John C. Bischof (Annals of Biomedical Engineering, 2008)

Influence of plant growth regulators on growth, morpho-physiological characters and yield of summer sesame (Sesamum indicum L. cv. Rama) under moisture stress - Arjun Kumr Garai; Jayanta Kumar Datta (Acta Physiologiae Plantarum, 1999)